Women's Integration into the Argentine Armed Forces and Redefinition of Military Service. What does Military Democratization mean? - Frederic, Sabina Andrea (2015)
In 2006, the distinction between « recruiting » and « integrating » women into the Armed Forces became part of the political agenda of the Ministry of Defense. Later, in 2007, the Ministry created the Gender Policy Council for the Defense (the Council) where military officers and NCOs, academics (mostly women) and members of non-governmental organizations debated thoroughly on the signification of recruiting women into military life, promoting different forms of integration. There was a general consensus on the need to move from the issue of incorporating female military personnel according to vacancies and vacancy distribution to the problem of the conditions that hindered their integration into military life. A more difficult question arose during the debate, namely, to what extent could the social and cultural values of the civil sphere be transferred to the military profession. The possible forms of integration of women into the Armed Forces reflected the current trend in the military profession in Argentina and showed the significance that the gender issue had acquired in this sphere.